1986
DOI: 10.1357/002224086788401648
|View full text |Cite
|
Sign up to set email alerts
|

Observations of the horizontal separation of the salinity core and the current core in the Atlantic Equatorial Undercurrent

Abstract: From January to June 1979 the R. V. Meteor surveyed the central equatorial Atlantic on a line along 22W from 2S to 3N. By means of CTD and horizontal deflection measurements of a towed undulating instrument, the "Delphin," a time series of the horizontal location of the velocity core of the Equatorial Undercurrent and its related salinity maximum could be obtained. The time interval of observations between the 11 "De1phin" sections ranged from 5 to 30 days. In the mean the salinity maximum is located 30 Ian so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The most conspicuous features on the average section along 23øW (Figure 2) are also found on individual cruises presented in Hisard and Hdnin [1987]. Fahrbach et al [1986] showed the association of the EUC core with a sMinity and oxygen maximum in 1979 data, and discussed the meridional separation between the salinity and current cores. This is also present here, and the off-equatorial salinities are lower with the thermochne maximum values being less at 3-4øN and 2-3øS than between 0 and løS.…”
Section: $1 Zonal Circulationmentioning
confidence: 54%
“…The most conspicuous features on the average section along 23øW (Figure 2) are also found on individual cruises presented in Hisard and Hdnin [1987]. Fahrbach et al [1986] showed the association of the EUC core with a sMinity and oxygen maximum in 1979 data, and discussed the meridional separation between the salinity and current cores. This is also present here, and the off-equatorial salinities are lower with the thermochne maximum values being less at 3-4øN and 2-3øS than between 0 and løS.…”
Section: $1 Zonal Circulationmentioning
confidence: 54%
“…The EUC is centered around the equator and in the thermocline, and is a relatively stable and quasi-permanent feature in both the Pacific and Atlantic Oceans (Izumo 2005:110;Philander 1980:191). It is a strong, "jet-like subsurface current," the source of which (in the Atlantic) is likely the high-salinity Northern Brazil Coastal Current (Fahrbach et al 1986:763; see also Bonhoure et al 2004). In the Gulf of Guinea it exists just under a westward flowing surface current (the SEC), and just above and north of it is the eastward surface flow of the Guinea Current (Bonhoure et al 2004;Philander 1980:202-203).…”
Section: The Equatorial Undercurrent and The Guinea Countercurrentmentioning
confidence: 99%